Top Incomes and the Measurement of Inequality in Egypt - Hlasny, Vladimir (Published by Oxford University Press on behalf of the World Bank, 2019)
This study exploits unprecedented access to income data and a combination of newly developed statistical methods to evaluate income inequality in Egypt and test for potential top incomes biases. Income inequality in Egypt is found to be low by regional and world standards; top incomes are found to follow the Pareto distribution and do not show anomalies compared to surveys worldwide. Correcting for top incomes biases increases the Gini coefficient significantly. The magnitude of the upward correction varies between 1.1 and 4.1 percentage points depending on the choice of correction method and welfare measure.